Staphylococcus lugdunensis Endocarditis in a 35-Year-Old Woman in Her 24th Week of Pregnancy - Mounir Khafaga; Karl-Patrik Kresoja; Berndt Urlesberger; Igor Knez; Philipp Klaritsch; David Benjamin Lumenta; Robert Krause; Dirk von Lewinski (Hindawi Limited, 2016)
Background. Infective endocarditis is associated with considerable morbidity and mortality. Guidelines addressing prophylaxis and management of infective endocarditis do not extensively deal with concomitant pregnancy, and case reports on infective endocarditis are scarce. This is the first published report of infective endocarditis by Staphylococcus lugdunensis in a pregnant woman. Case Presentation. We report a single case of a 35-year-old woman in her 24th week of pregnancy who was admitted to our intensive care unit with fever and suspected infectious endocarditis. Blood culture detected Staphylococcus lugdunensis. A vegetation and severe mitral regurgitation due to complete destruction of the valve confirmed the diagnosis. An interdisciplinary panel of cardiologists, maternal-fetal medicine specialists, cardiac and plastic surgeons, infectiologists, anesthesiologists, and neonatologists was formed to determine the best therapeutic strategy. Conclusions. Timing and indications for surgical intervention to prevent embolic complications in infective endocarditis remain controversial. This original case report illustrates how managing infective endocarditis by Staphylococcus lugdunensis particularly in the 24th week of pregnancy can represent a therapeutic challenge to a broad section of specialties across medicine. Critical cases like this require a thorough weighing of risks and benefits followed by swift action to protect the mother and her unborn child.